Clinical value of styrofoam fixation in intracranial tumor radiotherapy - Li, Bo; Bai, Fei; Yao, Xiaowei; Xu, Linlin; Zhao, Lina (Frontiers in Oncology, 2023)
Objective: To analyze the application value of two postural fixation techniques.(styrofoam combined with head mask and fixed headrest combined with head mask) in intracranial tumor radiotherapy via cone beam computed tomography (CBCT). Methods: This study included 104 patients with intracranial tumors undergoing radiotherapy. The patients were divided into two groups: Group A (54 cases with styrofoam fixation) and Group B (50 cases with fixed headrest fixation). The positional deviation in 3D space between the two groups was compared using CBCT. The set-up errors were expressed as median (25th percentile, 75th percentile)or M(p25, p75) since the set-up errors in all directions were not normally distributed,The Mann-Whitney U test was performed. Results: The age and gender of patients in the two groups were not significantly different. The set-up errors of A in lateral（X）, longitudinal（Y）, vertical（Z）, and yaw（Rtn） axes were 1.0 (0,1) mm, 1.0 (0,1) mm, 1.0 (0,2) mm, and 0.4 (0.1, 0.8) degrees, respectively while the set-up errors of B were 1.0 (0,1) mm, 1.0 (1,2) mm, 1.0 (0,2) mm, and 0.5 (0.15,0.9) degrees, respectively. Moreover, patients in the styrofoam group had significantly smaller set-up errors in the Y-axis than patients in the headrest group (p=0.001). However, set-up errors in the X, Z, and Rtn axes were not significantly different between the two groups. The expansion boundaries of the target area in the X, Y, and Z directions were 1.77 mm, 2.45 mm, and 2.47 mm, respectively. The outer expansion boundaries of the headrest group were 2.03 mm, 3.88 mm, and 2.57 mm in X, Y, and Z directions, respectively. The set-up times of groups A and B were (32.71±5.21) seconds and (46.57±6.68) seconds, respectively (p=0.014). Patients in group A had significantly better comfort satisfaction than patients in group B (p=0.001). Conclusion: Styrofoam plus head thermoplastic mask body fixation technique has a higher positional accuracy in intracranial tumor radiotherapy than headrest plus head thermoplastic mask fixation. Besides, styrofoam plus head thermoplastic mask body fixation technique is associated with improved positioning efficiency, and better comfort than headrest plus head thermoplastic mask fixation, and thus can be effectively applied for intracranial tumor radiotherapy positioning.